2018
DOI: 10.1002/alr.22173
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous anesthesia improves intraoperative visualization during surgery for high‐grade chronic rhinosinusitis: a double‐blind randomized controlled trial

Abstract: TIVA contributes to improved intraoperative visualization and decreased blood loss in patients undergoing ESS for high-grade inflammatory sinus disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 29 publications
2
55
0
1
Order By: Relevance
“…Duration of surgery was similar among the TIVA and IA groups (WMD −3.31, 95% CI −7.95, 1.34, I 2 = 69%, P = 0.16) based on 13 RCTs (Fig. A).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Duration of surgery was similar among the TIVA and IA groups (WMD −3.31, 95% CI −7.95, 1.34, I 2 = 69%, P = 0.16) based on 13 RCTs (Fig. A).…”
Section: Resultsmentioning
confidence: 88%
“…A). Pooled analysis from two RCTs of the 10‐point Wormald scale for surgical visibility also demonstrated significantly lower scores for the TIVA group compared to IA (WMD −0.73, 95% CI −1.28, −0.19, I 2 = 30%, P = 0.009) (Fig. A).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous techniques have been applied to minimize blood loss and improve endoscopic visualization during ESS, including the reverse Trendelenburg position and total intravenous anesthesia (TIVA). In addition, numerous medications have been used to improve hemostasis during surgery including topical 1:1000 epinephrine and infiltration with lidocaine with 1:100,000 epinepherine …”
Section: Wormald Surgical Field Grading Scalementioning
confidence: 99%
“…In addition, numerous medications have been used to improve hemostasis during surgery including topical 1:1000 epinephrine and infiltration with lidocaine with 1:100,000 epinepherine. [1][2][3][4][5] Numerous studies have demonstrated the efficacy and safety of topical 1:1000 epinephrine in preparation of ESS. [6][7][8] Traditional teaching has also advocated for the local infiltration of lidocaine with 1:100,000 epinephrine in an effort to diminish blood loss and improve endoscopic 6 10 points of ooze, obscuring surface (sphenoid fills in 50 seconds) 7 Mild bleeding/oozing from entire surgical surface with slow accumulation of blood in the postnasal space (sphenoid fills by 40 seconds) 8 Moderate bleeding from entire surgical surface with moderate accumulation of blood in postnasal space (sphenoid fills by 30 seconds) 9 Moderately severe bleeding with rapid accumulation of blood in the postnasal space (sphenoid fills by 20 seconds) 10 Severe bleeding with nasal cavity filling rapidly (sphenoid fills in <10 seconds)…”
mentioning
confidence: 99%